Формування факторів економічної оцінки "розумного підприємства": економічний та менеджерський підходи - Перерва, Петро Григорович; Мащенко, Марина Анатоліївна; Ткачова, Надія Петрівна; Ларка, Людмила Сергіївна (Український державний університет залізничного транспорту, 2024)
У статті розглянуто ключові аспекти економічної оцінки «розумного підприємства», що ґрунтуються на сучасних досягненнях у сфері цифрових технологій та інноваційного менеджменту. Проаналізовано фактори, які впливають на ефективність функціонування таких підприємств, включаючи використання штучного інтелекту, автоматизації, інтернету речей (IoT) та великих даних (Big Data). Окрема увага приділяється методам управління та економічної оцінки, які можуть забезпечити конкурентоспроможність і стійкий розвиток розумних підприємств. Визначено основні економічні та управлінські підходи, що сприяють підвищенню їх продуктивності та інноваційної здатності в умовах цифрової трансформації.

The article discusses the key aspects of the economic evaluation of the «smart enterprise», based on modern achievements in the field of digital technologies and innovation management. The factors influencing the efficiency of functioning of such enterprises are analyzed, including the use of artificial intelligence, automation, the Internet of Things (IoT) and big data (Big Data). Two approaches to the economic evaluation of «smart enterprise» – economic and managerial – have been proposed. The economic approach focuses on assessing the financial performance of an enterprise through the analysis of indicators such as profitability, resource productivity and asset turnover. The managerial approach focuses more on management decisions and resource optimization. It covers the use of labor and material resources, the analysis of management indicators such as the efficiency of working capital, labor productivity and the estimation of costs per unit of production. The article proves that both economic and managerial approaches complement each other and allow for a comprehensive assessment of the effectiveness of a "smart enterprise", which is especially important in the context of digital transformation of the economy. Particular attention is paid to management and economic evaluation methods that can ensure the competitiveness and sustainable development of smart enterprises. The main economic and managerial factors that contribute to increasing their productivity and innovation ability in the context of digital transformation are identified and substantiated in detail. The proposed factors of economic efficiency of the «smart enterprise» are based on the use of modern technologies and the integration of automation into business processes. These characteristics allow the enterprise to achieve significant resource optimization, increased productivity and cost reduction.
Formation of factors of economic evaluation of "smart enterprise": economic and managerial approaches
Keywords: розумне підприємство; економічна оцінка; фактори; економіка; менеджмент; ефективність; smart enterprise; economic assessment; factors; economics; management; efficiency